Experimental Studies of Mechanical-Electrical Transformations during the Destructive Processes Developing in Dielectric Materials - Bespal’ko, A.A.; Utsyn, G.E.; Fedotov, P.I. (Karagandy University of the name of acad. E.A. Buketov, 2022)
A mechanical-electrical method for testing fractures developing within the stress-strain state changes of dielectric rock samples, as an example, is discussed here. The paper discusses the results of numerical and experimental studies of changes in the electromagnetic responses parameters under the pulse deterministic acoustic excitation of rock samples with different composition and texture. The paper presents the results of mathematical calculations of the stress concentration on cracks located along and across the sample axis, perpendicular to which deterministic acoustic pulses were introduced. The cracks presented in the sample volume are stress concentrators. With a different number and sizes of cracks perpendicular to the propagation of an acoustic pulse, the intensity of stresses and their type differ significantly. This circumstance indicates the influence of the structure of the samples and their dielectric properties on the parameters of electromagnetic signals when recording the results of mechanical and electrical transformations. Thus, the use of the method of mechanical-electrical transformations under compression can be used in testing the processes of the onset of crack formation and the development of fracture in solid-state dielectric materials and products.
Диэлектрлік материалдардағы деструктивті процестердің дамуы кезіндегі механикалық және электрлік түрлендірулерді сандық және тәжірибелік зерттеулер
Численное и экспериментальное исследования механико-электрических преобразований при развитии деструктивных процессов в диэлектрических материалах
Keywords: dielectrics; rocks; numerical modeling; acoustic impact; uniaxial compression; electromagnetic emission; mechanoelectric transformations